2003
DOI: 10.1111/j.1432-2277.2003.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Location and sanitation of dental foci in liver transplantation

Abstract: The literature describes various treatment concepts for the pre-operative sanitation of septic foci in the oromaxillofacial area prior to liver transplantation. There are no uniform guidelines, and so far, a connection between dental foci and postoperative infection after transplantation has not yet been proven. Taking into account the complications occurring during focus sanitation, the appropriate extent of, and the most suitable point of time for, focus sanitation have to be ascertained. The clinical and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 18 publications
3
21
0
9
Order By: Relevance
“…This imposes the need of dental help long before the surgery and not just prior the operation (3,5,6,10).…”
Section: Resultsmentioning
confidence: 99%
“…This imposes the need of dental help long before the surgery and not just prior the operation (3,5,6,10).…”
Section: Resultsmentioning
confidence: 99%
“…The authors mention that the main concern before the transplantation is to eliminate oral foci of infection, such as those of periapical and periodontal origin (1,4,13).…”
Section: Medinformmentioning
confidence: 99%
“…The risk of operating a cirrhotic patient should be considered more carefully, because of the possibility of bleeding and infection [25]. A German study with 80 liver transplant candidates reported poorer oral health among the alco holics.…”
Section: Oral Health In Liver Transplantation Candidates and Transplamentioning
confidence: 99%
“…High rate of complications after treatment prior to transplantation, frequently among alcoholic and Child-Pugh stage C patients, recommends extra care with radical prophylactic dental sanitation. According to these authors, only absolutely necessary sanitation should be carried out prior to transplantation [25].…”
Section: Oral Health In Liver Transplantation Candidates and Transplamentioning
confidence: 99%
See 1 more Smart Citation